1996
DOI: 10.5902/19805098324
|View full text |Cite
|
Sign up to set email alerts
|

Produção de <i>Pinus taeda </i>L. na região de Cambará do Sul, RS.

Abstract: RESUMOO trabalho teve como objetivo estruturar a produção de uma floresta de Pinus taeda L., localizada na região de Cambará do Sul, RS, de acordo com a idade, potencial de produção dos sítios e manejo aplicado. Para tanto foram coletados dados em parcelas temporárias, permanentes e de análise de tronco. Funções matemáticas foram ajustadas para estimar o desenvolvimento do povoamento remanescente após o desbaste e o fator K-Magin foi usado para corrigir o volume dos desbastes, e variou de 0,76 a 0,78. Os resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
1
9

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 0 publications
1
4
1
9
Order By: Relevance
“…There was a slight trend of form factor reduction with diameter classes increase (Table 3). Mainardi et al (1996) evaluated Pinus taeda form factor in Rio Grande do Sul State, stating variation according to age in relationship to total height and dbh increments. Trees that were four years old had a form factor of 0.79, whereas the form factor dropped to 0.5 at 16 years old, demonstrating tapering trend and, consequently, form factor value reduction.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There was a slight trend of form factor reduction with diameter classes increase (Table 3). Mainardi et al (1996) evaluated Pinus taeda form factor in Rio Grande do Sul State, stating variation according to age in relationship to total height and dbh increments. Trees that were four years old had a form factor of 0.79, whereas the form factor dropped to 0.5 at 16 years old, demonstrating tapering trend and, consequently, form factor value reduction.…”
Section: Resultsmentioning
confidence: 99%
“…One possibility of improving form factor volume estimation would be to stratify trees by diameter class and to apply such estimation factors, since several studies have shown that the form factor varies with age (Kohler, 2013) and diameter class (Mainardi et al, 1996). This would guarantee simplicity without much use of statistics, and results comparable to those generated by the regression models will be obtained.…”
Section: Resultsmentioning
confidence: 99%
“…(FERNANDES e BACKES, 1998) a 7,7 Mg ha -1 de matéria seca ao ano (FIGUEIREDO FILHO et al, 2003) , o que representa considerável estoque de carbono (MAINARDI et al, 1996). Em outro estudo na região de Curitiba, PR, verificou-se acúmulo de 60,9 Mg ha -1 de C na biomassa da bracatinga após oito anos (FEISTAUER et al, 2004).…”
Section: Resultsunclassified
“…Esses valores estão dentro do intervalo do que foi observado por Mainardi et al (1996) As ITC para a área basal são 9, 10 e 11 anos, as quais indicam a idade ideal para o desbaste, próximas da idade de desbaste de 10 anos, empregada pela empresa. Nos povoamentos florestais, as árvores começam a competir, primeiramente, em relação à área basal do que em volume, justificando a realização do desbaste antes do povoamento atingir a ITC no volume.…”
Section: Tabela 4 Tableunclassified